Income-dependent equivalence scales and choice theory implications for poverty measurement - Christos Koulovatianos; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Equivalence Scales are a tool for removing the heterogeneity of household sizes in the measurement of inequality, and affect poverty assessments and poverty lines. We address the disadvantage that poor households may suffer due to their reduced ability to share goods within the household. This disadvantage is important to estimate and embed in standard analysis, as it seems to have a substantial quantitative impact on the measurement of poverty. We also suggest that future research on the role of subsistence incomes of different household types in utility functions may shed light on explanations for poverty and may guide anti-poverty policies.
Keywords: I32; D14; D63; D15; 330; Equivalent incomes; household-size economies; inequality; demographics and poverty; child costs; Generalized Equivalence Scale Exactness